Russian interferon α-2b drug in the treatment of chronic hepatitis C - N. B. Kovaleva (Российский журнал гастроэнтерологии, гепатологии, колопроктологии)
Aim of investigation. To study efficacy and safety of domestic recombinant interferon α-2b Altevir® in combination to ribavirin in previously untreated patients with chronic hepatitis C (CHC).Material and methods. Retrospective treatment results rating of 85 patients (49 men (57%) and 36 women (43%)) was carried out. All patients received 3 million IU per day of Altevir® subcutaneously and ribavirin (Ribapeg). Treatment duration was 48 wks for patients with 1-st genotype of hepatitis C virus (HCV) and 24 wks — for patients with 2nd and 3а HCV genotypes. Results. Aviremia in 24 wks after the end of therapy (sustained virologic response — SVR) has been achieved in 100% of patients with 2-st HCV genotype, in 95,8% patients with 3а HCV genotype and in 65,6% patients with 1b HCV genotype. The registered adverse effects, well-known for interferon α-2b therapy, as a rule, were mild or moderate, AVT cancellation was not required in any patient.Conclusions. For patients with CHC with 2-st, 3а HCV genotypes and favorable prognosis of virologic response at combined AVT, including Altevir® and ribavirin, SVR frequency can reach 100 and 96% respectively. At AVT, including Altevir® and ribavirin to CHC patients with 1b genotype of HCV and favorable prognosis of virologic response, 66% SVR rate can be achieved.